Optimum Network Reconfiguration using Grey Wolf Optimizer - Ridha Djamel Mohammedi; Rabie Zine; Mustafa Mosbah; Salem Arif (Universitas Ahmad Dahlan, 2018)
The objective of this paper is to determine an optimal network reconfiguration that presents the minimum losses considering network constraints using Grey Wolf Optimizer (GWO) algorithm. The proposed algorithm was tested using some standard networks (33_bus, 69_bus, 84_busand 118_bus).